Benign breast pathology in patients attended at Hospital Nacional Arzobispo Loayza Gynecology Oncology Service - Grados, Jesús Ernesto Marreros (2013)
Objectives: To determine the most common benign breast disease by histopathology diagnosis and its characteristics. Design: Observational, retrospective study. Setting: Hospital Nacional Arzobispo Loayza, Lima, Peru. Participants: Women with benign breast disease. Interventions: Between January and December 2012, benign breast disease with pathology diagnosis was related to localization, size and most frequent age interval. Main outcome measures: Benign breast disease pathology characteristics. Results: In 175 women fibroadenoma was the most frequent benign breast tumor, present in 61 cases, mainly in women 10-39 year-old. The tumor was single in 158 (90%) patients (158), the left breast was the most affected in 84 (48%) patients, with tumors ranging from 1 to 3 cm (60% of patients), the radius of location at 2, 3 and 10. Conclusions: The most common breast benign tumor was fibroadenoma. Its finding is necessary for pathologic examination to exclude carcinoma. Keywords: Benign breast tumor, fibroadenoma.